An Adaptive Feedback Canceller for Full-Duplex Relays Based on Spectrum Shaping - R. López-Valcarce; Emilio Antonio-Rodríguez; C. Mosquera; Fernando Pérez-González (IEEE J. Selected Areas in Communications, 2012)
Although full-duplex relaying schemes are appealing in order to improve spectral efficiency, simultaneous reception and transmission in the same frequency results in selfinterference, distorting the retransmitted signal and making the relay prone to oscillation. Current feedback cancellation techniques by means of adaptive filters are hampered by the fact that the useful and interference signals are highly correlated. We present a new adaptive algorithm which effectively and blindly restores the spectral shape of the desired signal. In contrast with previous schemes, the novel adaptive feedback canceller has low complexity, does not introduce additional delay in the relay station, and partly compensates for multipath propagation.
Keywords: adaptive signal processing; dynacs; full duplex